Production scheduling system for job shop enteprise using ant colony optimization approach - Ho, Fu Haw; Masine, Md Tap, Assoc. Prof. Dr. (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.